2019
DOI: 10.18821/0869-2084-2019-64-2-117-121
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Laboratory Methods of Diagnostic of Purulent Bacterial Meningitis

Abstract: According to the World Health Organization, every year about 1 million cases of purulent bacterial meningitis (PBM) are registered in the world, of which 200 thousand cases end in death. Bacterial meningitis is polyethiologic, which makes the task of determining the pathogen the main in the organization of epidemiological surveillance, treatment regimens, planning of preventive and anti-epidemic measures. The quality of laboratory diagnostics has a key influence on this. The true incidence of meningitis of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A study found that C-reactive protein (CRP), tumor necrosis factor (TNF)-α, and procalcitonin (PCT) levels can be potential markers. However, their application in clinical diagnosis has some limitations ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study found that C-reactive protein (CRP), tumor necrosis factor (TNF)-α, and procalcitonin (PCT) levels can be potential markers. However, their application in clinical diagnosis has some limitations ( 5 ).…”
Section: Introductionmentioning
confidence: 99%